Motor Areas Show Altered Dendritic Structure in an Amyotrophic Lateral Sclerosis Mouse Model - Fogarty, Matthew J.; Mu, Erica W. H.; Lavidis, Nickolas A.; Noakes, Peter G.; Bellingham, Mark C. (Frontiers in Neuroscience, 2017)
Objective: Motor neurons (MNs) die in amyotrophic lateral sclerosis (ALS), a clinically heterogeneous neurodegenerative disease of unknown aetiology. In human or rodent studies, MN loss is preceded by increased excitability. As increased neuronal excitability correlates with structural changes in dendritic arbors and spines, we have examined longitudinal changes in dendritic structure in vulnerable neuron populations in a mouse model of familial ALS. Methods: We used a modified Golgi-Cox staining method to determine the progressive changes in dendritic structure of hippocampal CA1 pyramidal neurons, striatal medium spiny neurons, and resistant (trochlear, IV) or susceptible (hypoglossal, XII; lumbar) MNs from brainstem and spinal cord of mice over-expressing the human SOD1G93A (SOD1) mutation, in comparison to wild-type (WT) mice, at 4 postnatal (P) ages of 8-15, 28-35, 65-75 and 120 days. Results: In SOD1 mice, dendritic changes occur at pre-symptomatic ages in both XII and spinal cord lumbar MNs. Spine loss without dendritic changes was present in striatal neurons from disease onset. Spine density increases were present at all ages studied in SOD1 XII MNs. Spine density increased in neonatal lumbar MNs, before decreasing to control levels by P28-35 and were decreased by P120. SOD1 XII MNs and lumbar MNs, but not trochlear MNs showed vacuolization from the same time-points. Trochlear MN dendrites were unchanged. Interpretation: Dendritic structure and spine alterations correlate with the neuro-motor phenotype in ALS and with cognitive and extra-motor symptoms seen in patients. Prominent early changes in dendritic arbors and spines occur in susceptible cranial and spinal cord MNs, but are absent in MNs resistant to loss in ALS.